2014
DOI: 10.1002/cpp.1918
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment, Shame‐Proneness and Self‐Criticism in Social Anxiety Disorder: A Sequential Mediational Model

Abstract: Previous research has shown that histories of emotional abuse and emotional neglect predict social anxiety symptoms, but the mechanisms that underlie these associations are not clear. Using psycho-evolutionary and emotion-focused perspectives, the findings of the current study suggest that shame and self-criticism play an important role in social anxiety and may mediate the link between emotional abuse and symptoms. These findings also suggest that therapeutic interventions specifically targeting shame and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 74 publications
6
70
0
1
Order By: Relevance
“…Self‐criticism is a self‐evaluative process where individuals judge themselves in a negative or harsh way (Shahar, Szsepsenwol, et al ., ). Self‐criticism has been described as a transdiagnostic process; it is associated with a wide range of problems including depression (Luyten et al ., ), social anxiety (Shahar, Doron, & Szepsenwol, ), and eating disorders (Fennig et al ., ). Since self‐critical individuals have poorer outcomes after depression treatment (Marshall, Zuroff, McBride, & Bagby, ; Rector, Bagby, Segal, Joffe, & Levitt, ), research has begun to focus on treatments specifically targeting self‐criticism (see Kannan & Levitt, for a review, as well as Shahar et al ., ; Shahar, Szsepsenwol, et al ., , e.g., treatment studies).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐criticism is a self‐evaluative process where individuals judge themselves in a negative or harsh way (Shahar, Szsepsenwol, et al ., ). Self‐criticism has been described as a transdiagnostic process; it is associated with a wide range of problems including depression (Luyten et al ., ), social anxiety (Shahar, Doron, & Szepsenwol, ), and eating disorders (Fennig et al ., ). Since self‐critical individuals have poorer outcomes after depression treatment (Marshall, Zuroff, McBride, & Bagby, ; Rector, Bagby, Segal, Joffe, & Levitt, ), research has begun to focus on treatments specifically targeting self‐criticism (see Kannan & Levitt, for a review, as well as Shahar et al ., ; Shahar, Szsepsenwol, et al ., , e.g., treatment studies).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the sequential roles of shame and self-criticism, according to the theoretical accounts described above and empirical research (e.g., Shahar, Doron, & Szepsenwol, 2014), self-criticism usually functions as a coping mechanism to cope with feelings of shame-a safety strategy focused on the self (in order to maintain the self-others connection, thus avoiding rejection/exclusion) that in turn leads to unintended consequences such as exacerbation of symptoms (including shame) and social isolation. In the present study, we aimed at exploring the associations between external shame, self-criticism, social stress reactivity, and social functioning in a sample of people with a psychotic disorder.…”
Section: Key Practitioner Messagementioning
confidence: 99%
“…Social stress reactivity is conceptualized as an independent variable because it concerns a pre-existing vulnerability arising from a hyperactive threat system influenced by more distal factors (such as genetic, familial, and early experiences). Concerning the sequential roles of shame and self-criticism, according to the theoretical accounts described above and empirical research (e.g., Shahar, Doron, & Szepsenwol, 2014), self-criticism usually functions as a coping mechanism to cope with feelings of shame-a safety strategy focused on the self (in order to maintain the self-others connection, thus avoiding rejection/exclusion) that in turn leads to unintended consequences such as exacerbation of symptoms (including shame) and social isolation.…”
Section: Key Practitioner Messagementioning
confidence: 99%
“…As anticipated, BIS demonstrated positive correlations with FNE, SCR, and SPP (Fee & Tangney, 2000;Joireman, 2004;Shahar et al, 2015). Furthermore, results of the moderated serial mediation analysis indicated that BIS sensitivity significantly moderated the indirect effect of shame on SPP through FNE and SCR.…”
Section: Shame Bis and Internalizing Responsesmentioning
confidence: 59%
“…Indeed, self-criticism has been posited to serve as a defensive response to shame, intended to discourage the shamed-individual from engaging in social risks that may further damage their social standing (Gilbert, 1998;Gilbert & Irons, 2005). In support of this notion, Shahar, Doron, and Szepsenwol (2015) found that a history of childhood maltreatment predicted higher shame-proneness, which in turn predicted increased self-criticism. In turn, higher levels of self-criticism predicted higher levels of social anxiety.…”
Section: Perfectionismmentioning
confidence: 84%